2020
DOI: 10.1097/pas.0000000000001452
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Hepatic Manifestations of Common Variable Immunodeficiency

Abstract: Common variable immunodeficiency (CVID) has a heterogenous clinical presentation and can be challenging to diagnose. Distinct histologic changes have been linked with CVID in several organ systems, which can help identify the correct diagnosis. In this study we review a cohort of hepatic CVID biopsies, to better define the spectrum of histologic and biochemical alterations. We reviewed 26 liver biopsies from 24 patients with CVID, obtained at 4 institutions between 2010 and 2019. Histologic slides were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…As in our study, the liver function test results in that study were slightly abnormal, especially ALP and AST. The classic features of primary biliary cholangitis, which was not observed in our sample, were observed in two of the biopsies evaluated by those authors ( 57 ). Other studies have shown that, in patients with NRH but without CVID, the changes in transaminases and canalicular enzymes are modest, highlighting ALP, which can present a progressive increase even when liver function is preserved ( 25 , 58 ).…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…As in our study, the liver function test results in that study were slightly abnormal, especially ALP and AST. The classic features of primary biliary cholangitis, which was not observed in our sample, were observed in two of the biopsies evaluated by those authors ( 57 ). Other studies have shown that, in patients with NRH but without CVID, the changes in transaminases and canalicular enzymes are modest, highlighting ALP, which can present a progressive increase even when liver function is preserved ( 25 , 58 ).…”
Section: Discussionmentioning
confidence: 40%
“…In another study of CVID patients, Crotty et al. ( 57 ) diagnosed PH in 75% of those who underwent liver biopsy. In that study, there was also mild-to-moderate portal inflammation in 75% of the patients and lobular inflammation in approximately 70%.…”
Section: Discussionmentioning
confidence: 96%
“…Dysregulation of bile acid metabolism related to bacterial dysbiosis has been reported for several conditions (72,73) including a CVID murine model (32). Frequent CVID complications, such as malabsorbtion and/or liver diseases (74)(75)(76), also indicate dysregulation of bile acid metabolism. In fact, splenomegaly was frequent among our CVID patients.…”
Section: Differences In Cvid Metabolomementioning
confidence: 99%
“…Liver disease is a frequent and underrecognized complication in patients with CVID and can be a consequence of recurrent infectious insults, malignancy, and/or immune dysregulation impacting the liver. The most prevalent liver pathology in patients with CVID is nodular regenerative hyperplasia (NRH), which affects 41%-87% of patients with CVID who undergo liver biopsy (3)(4)(5)(6). NRH is believed to be mediated through T-cell infiltration of the sinusoidal endothelium, causing intra-hepatic vasculopathy.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with CVID, NRH is characterized histologically by a nodular pattern of alternating areas of hepatic plate expansion and atrophy. NRH-like changes are often accompanied by other histologic features of CVID such as a sinusoidal lymphocytic infiltrate, mild portal and lobular inflammation, and variably prominent sinusoidal fibrosis (6). NRH-like changes may be present on liver biopsy even when clinical manifestations are subtle (such as mildly elevated liver enzymes), making improved diagnostic modalities essential.…”
Section: Introductionmentioning
confidence: 99%